Validation of pharmaceutical information systems: general provisions - K. A. Koshechkin; E. V. Gladkaya; Ya. Yu. Kondratieva (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Nternational practices comprise integrated common approaches to validation of information systems, used in pharmaceutical industry by various organizations and that affect the results of their work. The purpose ofvalidation is to assure that the results, obtained with the help of an information system are reliable. Validated system ensures accurate results and reduces the risk of errors. The article describes basic principles of the validation of pharmaceutical information systems. The principles are constituted on the basis of international requirements of OMCL system and international standards of ISO system. The article provides the classification information systems used in pharmaceutical organizations. It also describes basic concepts of validation of information systems, such as version management, validation testing, change management, requirement consideration. Basic requirements for application of risk management system to creation of concept devoted to pharmaceutical information system validation are also provided.